Science and mathematics teachers of the future - Michelsen, Claus (2008)
This paper presents the project Science and Mathematics Teachers of the Future. The aim of the project is to develop and implement a graduate level equivalent degree program in mathematics and science instruction for in-service teachers of lower secondary education. This aim is achieved in the programme through involving the teachers in design, implementation and evaluation of innovative instructional sequences, which deals with a wide range of aspects of mathematics and science, e.g. modern science and the importance of science in society. In the program contemporary science and mathematics education research serves as a basis for the design and development of warranted practices with which the teachers may experiment in their classroom. We will focus on the outcomes of offering a program which is intimately tied to (i) contemporary science and mathematics education research, (ii) modern science and mathematics and (iii) the teacher’s practices in the classroom. - Este artigo apresenta o projecto Professores de Ciência e de Matemática do Futuro. O objectivo deste projecto consiste em desenvolver e implementar um programa de graduação em educação de matemática e ciências destinado a professores dos primeiros anos do ensino secundário (3º ciclo do ensino básico em Portugal). Este objectivo é alcançado no programa através do envolvimento dos professores na concepção, implementação e avaliação de sequências de ensino inovadoras, relacionadas com um leque alargado de aspectos de matemática e ciências como, por exemplo, a ciência moderna e a importância da ciência na sociedade. Neste programa, a investigação contemporânea em educação de ciência e matemática serve de base à concepção e desenvolvimento de práticas que os professores poderão experimentar nas suas aulas. Neste texto, centramo-nos nos resultados da oferta de um programa intimamente ligado: (i) a investigação contemporânea em educação de matemática e ciência; (ii) a ciência e matemática modernas e (iii) à prática lectiva dos professores.